2021
DOI: 10.1177/00368504211054992
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect and possible mechanisms of ultrashort wave diathermy on myogenic contracture in a rabbit model

Abstract: The purpose of this study was to determine the preventive effect of ultrashort wave diathermy on immobilization-induced myogenic contracture and to explore its underlying mechanisms. Forty-two rabbits were randomly assigned into control (Group C), immobilization (Group I, which was further divided into one week, Group I-1; two weeks, Group I-2; and four weeks, Group I-4, subgroups by the length of immobilization) and ultrashort wave prevention (Group U, which was further divided into one week, Group U-1; two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In order to observe the natural process of joint contracture, we established an animal model using immobilization by aluminum plates. Joint contracture is characterized by a reduction of joint range of motion compared with normal joints [ 34 , 35 ], thus decreased join range of motion represents increased degree of joint contracture. Previous studies have suggested that joint contracture occur within 1 week of knee joint immobilization and progress in a time-dependent manner [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to observe the natural process of joint contracture, we established an animal model using immobilization by aluminum plates. Joint contracture is characterized by a reduction of joint range of motion compared with normal joints [ 34 , 35 ], thus decreased join range of motion represents increased degree of joint contracture. Previous studies have suggested that joint contracture occur within 1 week of knee joint immobilization and progress in a time-dependent manner [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%